Staphylococcal Cassette Chromosome mec, Evolution and Genetic Lines of Methicillin Resistant Staphylococcus aureus - V. V. Gostev; S. V. Sidorenko (Антибиотики и Химиотерапия, 2020)
Methicillin resistant Staphylococcus aureus (MRSA) is the main pathogen of hospital- and community-associated infections. Methicillin resistance is due to mecA gene located in a mobile complex element, staphylococcal cassette chromosome mec (SCCmec). The structure of the staphylococcal cassettes is diverse. At present eleven types of the cassettes are described. Types I-IV SCCmec are always associated with epidemiologically significant genetic lines of Staphylococcus. Thus, the pandemic hospital-associated MRSA (HA MRSA) belonging to CC5 and CC8 are of the types I-III SCCmec. The prevalence of virulent community-associated MRSA (CA MRSA) in many regions of the world is first of all connected with the characteristics of the type IV SCCmec structure and the presence of a recently described arginine catabolic mobile element (ACME) increasing the colonization activity of Staphylococcus. The review presents the up-to-date data on the origin, genetic structure and classification of SCCmec. Global genetic lines of MRSA are described and the problem of CA MRSA is discussed.